2002
DOI: 10.1111/j.1708-8240.2002.tb00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of Bis‐acryl Composite Provisional Material Repaired with Flowable Composite

Abstract: Repair of bis-acryl composite provisional material with a flowable composite is effective, expedient, and inexpensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 10 publications
1
54
0
3
Order By: Relevance
“…The finding is in agreement with the results of other studies. 15,18 However, further studies are needed to incorporate more materials to confirm this finding and to elucidate the mechanism.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The finding is in agreement with the results of other studies. 15,18 However, further studies are needed to incorporate more materials to confirm this finding and to elucidate the mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…15 However, several studies showed that heat-cured PMMA denture-base resin was better for use with MMA-based repair resin compared with non-MMA-based resin. [16][17] While Gregory and others 18 found that the repairs of resin composite with identical matrix chemistry did not produce bond strengths greater than those with a 511 B In the current study, both self-cured (Alike) and heat-cured (Namilon) PMMA resins showed higher bond strengths with methacrylate-based repair resin, regardless of whether the curing mode of the repair resin was self-cured or light-cured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adhesives promote penetration of solvent systems and of monomers into the composite surface, depending on the degree of hydration and the chemical affinity of materials, and create a non-polymerized oxygen inhibition layer that could ultimately promote adhesion of new composites [32,33]. However, the study of Hagge et al [34] showed that the shear bond strength values of the flowable composite resin were significantly higher in surface treatment with sandblasting alone than with the combination of sandblasting and adhesive monomer. The results of the present study correspond well with those of the earlier studies in the composite resin.…”
Section: Discussionmentioning
confidence: 92%
“…If a composite repair tends to fracture within the original composite (cohesive fracture), one can assume the selected protocol to be appropriate to bear the occlusal loads. The location of the repair failure within the repaired material itself, rather than at the adhesive surface, suggests a better bond 16) . Nevertheless, shear bond strength tests may cause cohesive fractures of the substrate.…”
Section: ⅳ Discussionmentioning
confidence: 99%